2016
DOI: 10.1073/pnas.1522572113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of collagen recognition by human osteoclast-associated receptor and design of osteoclastogenesis inhibitors

Abstract: Human osteoclast-associated receptor (OSCAR) is an immunoglobulin (Ig)-like collagen receptor that is up-regulated on osteoclasts during osteoclastogenesis and is expressed in a range of myeloid cells. As a member of the leukocyte receptor complex family of proteins, OSCAR shares a high degree of sequence and structural homology with other collagen receptors of this family, including glycoprotein VI, leukocyte-associated Ig-like receptor-1, and leukocyte Ig-like receptor B4, but recognizes a unique collagen se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 47 publications
1
37
1
1
Order By: Relevance
“…Of interest, collagen has been recently demonstrated to act as a ligand for a number of stimulatory and inhibitory receptors in this family, including osteoclast associated receptor (OSCAR), GPVI, and LAIR-1 [21][22][23]. The structural basis for collagen recognition by the immune receptors has been investigated in a number of studies [24][25][26][27], however some controversy regarding the alignment of collagen-recognition sites among different receptors exists.…”
Section: Leukocyte Receptor Complex (Lrc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest, collagen has been recently demonstrated to act as a ligand for a number of stimulatory and inhibitory receptors in this family, including osteoclast associated receptor (OSCAR), GPVI, and LAIR-1 [21][22][23]. The structural basis for collagen recognition by the immune receptors has been investigated in a number of studies [24][25][26][27], however some controversy regarding the alignment of collagen-recognition sites among different receptors exists.…”
Section: Leukocyte Receptor Complex (Lrc)mentioning
confidence: 99%
“…OSCAR is particularly important for osteoclast differentiation, as it acts as a critical co-stimulatory receptor for osteoclast formation and function [23,[26][27][28]. GPVI is mainly found in platelets and binds to collagen during the process of blood coagulation [21].…”
Section: Leukocyte Receptor Complex (Lrc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Se puede concluir afi rmando que el papel del calcio como elemento mineral es muy importante para el tejido óseo, Nosotros caminamos literalmente sobre nuestras reservas del calcio y este en conjunto con la Vitamina D sirve para edifi car el hueso de tal manera que, si bien es cierto que estos agentes se vienen cuestionando en algunos aspectos como seguridad cardiovascular entre otros, existen nuevos conceptos, especialmente para la Vitamina D que le dan nuevos aires posicionándola más como una hormona que como una vitamina y con acción pleiotró-pica por la multiplicidad de receptores celulares en los diferentes tejidos (387)(388)(389)(390), y que defi nitivamente tanto el calcio como la Vitamina D no son los elementos más potentes en el arsenal terapéutico contra la enfermedad, pero sus défi cits son los más sencillos de identifi car y los más fáciles de corregir. …”
Section: "Pensamos Que Tanto El Calcio Como La Vitamina D Son Elementunclassified
“…We took this observation and showed that a fragment was generated by MMP-2 and MMP-9, with MMP-9 further degrading it. ECM fragments that are generated by proteolysis or other processing and have biological activity in addition to or distinct from the parent ECM protein are termed matrikines or matricryptins [ 42 ]. To test whether the collagen matrikine had signaling activity, a peptide 20 amino acids downstream of the cleavage site was generated and tested for in vitro and in vivo activity.…”
Section: Adapting These Approaches To Clinical Samplesmentioning
confidence: 99%